2016
DOI: 10.1007/s00404-016-4201-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of MBL2 exon1 polymorphisms with high-risk human papillomavirus infection and cervical cancers: a meta-analysis

Abstract: Collectively, we suggest that the MBL2 gene exon1 polymorphisms are associated with increased risk of high-risk HPV infection and cervical cancer development among Caucasians. Additionally, no significant association was found between the MBL2 -550 H/L or -221 X/Y polymorphisms and HPV infection in Caucasians, but there may be potential links in Asians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Through a meta-analysis of existing data on CC, a recent study demonstrated that MspI and Ile462Val polymorphisms in CYP1A1 gene are potential risk factors for CC development [56]. Another study suggested a potential association between MBL2 gene exon1 polymorphisms and an increased risk of CC development [57]. Interestingly, studies of various populations in African countries, including South Africa, Zimbabwe, Morocco, Sudan, Tunisia, and Senegal, identified an association between CC risk and polymorphisms in TGFBT10C , TGFBc509T , HLADRB1 , CCR2V6L , IL-10-1082G / A , and FasR-1377G genes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Through a meta-analysis of existing data on CC, a recent study demonstrated that MspI and Ile462Val polymorphisms in CYP1A1 gene are potential risk factors for CC development [56]. Another study suggested a potential association between MBL2 gene exon1 polymorphisms and an increased risk of CC development [57]. Interestingly, studies of various populations in African countries, including South Africa, Zimbabwe, Morocco, Sudan, Tunisia, and Senegal, identified an association between CC risk and polymorphisms in TGFBT10C , TGFBc509T , HLADRB1 , CCR2V6L , IL-10-1082G / A , and FasR-1377G genes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the most common gynecological malignancies worldwide with an estimated 570,000 cases and 311,000 deaths in 2018 1. The causal role of high-risk human papillomavirus (HR-HPV) in cervical intraepithelial neoplasia (CIN) has been approved by various studies 2, 3. Especially, HPV16 is by far the most common type of carcinogenic globally, with the positivity rate of over 60% in cervical cancer patients 4.…”
Section: Introductionmentioning
confidence: 99%
“…Virtually, all cases of CC result from infection with the oncogenic strains of human papillomavirus (HPV) [ 3 , 4 ]. The majority of HPV infections are short-lived and resolve spontaneously [ 5 7 ]. However, in some individual cases, permanent infection will lead to development of a precancerous lesion, known as cervical intraepithelial neoplasia or adenocarcinoma in situ [ 5 ] Additional factors increasing the likelihood of the development of CC include tobacco smoking, long-term oral contraceptive use, high parity, early sexual intercourse, pollutants, and co-infection with type 2 herpes simplex virus or the human immunodeficiency virus [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%